Thermal performance of alumina filler reinforced intumescent fire retardant coating for structural application - Ahmad, F. (Institute of Physics Publishing, 2014)
In the modern construction, fire safety has significant consideration for the protection of people and assets. Several intumescent fire protection systems are in practice and have constrain of releasing toxic gases on degradation forms an insulating char layer protecting underlying substrate. An intumescent coating expands many times of its thickness on exposure to fire and protect the underlying substrate from fire. This study presents the results of thermal performance of an intumescent fire retardant coating (IFRC) developed for structural application. IFRC was developed using expandable graphite (EG), ammonium poly phosphate (APP) and melamine (MEL), epoxy resin Bisphenol-A (BPA) and hardener triethylenetetramine (TETA) were used as a binder as a curing agent. Char expansion of IFRC was measured by furnace fire test at 450°C, thermal performance was measured using a Bunsen burner at 950°C and temperature of substrate was recorded for 60 min at an interval of two min. Results showed that IFRC containing 3wt alumina showed char expansion X19. After one hour exposure of coating to heat, substrate temperature recorded was 154°C. X-ray Diffraction (XRD) results showed the presence of high temperature compounds present in the char of coating, considered responsible to reduce the penetration of heat to the substrate. © Published under licence by IOP Publishing Ltd.